Clinical evaluation of accommodation and ocular surface stability relevant to visual asthenopia with 3D displays. - Wee, Sung Wook; Moon, Nam Ju (BMC Ophthalmology, 2014)
Background: To validate the association between accommodation and visual asthenopia by measuring objective accommodative amplitude with the Optical Quality Analysis System (OQAS®, Visiometrics, Terrassa, Spain), and to investigate associations among accommodation, ocular surface instability, and visual asthenopia while viewing 3D displays.Methods: Fifteen normal adults without any ocular disease or surgical history watched the same 3D and 2D displays for 30 minutes. Accommodative ability, ocular protection index (OPI), and total ocular symptom scores were evaluated before and after viewing the 3D and 2D displays. Accommodative ability was evaluated by the near point of accommodation (NPA) and OQAS to ensure reliability. The OPI was calculated by dividing the tear breakup time (TBUT) by the interblink interval (IBI). The changes in accommodative ability, OPI, and total ocular symptom scores after viewing 3D and 2D displays were evaluated.Results: Accommodative ability evaluated by NPA and OQAS, OPI, and total ocular symptom scores changed significantly after 3D viewing (p = 0.005, 0.003, 0.006, and 0.003, respectively), but yielded no difference after 2D viewing. The objective measurement by OQAS verified the decrease of accommodative ability while viewing 3D displays. The change of NPA, OPI, and total ocular symptom scores after 3D viewing had a significant correlation (p < 0.05), implying direct associations among these factors.Conclusions: The decrease of accommodative ability after 3D viewing was validated by both subjective and objective methods in our study. Further, the deterioration of accommodative ability and ocular surface stability may be causative factors of visual asthenopia in individuals viewing 3D displays.